The nature of the white opaque substance within colorectal neoplastic epithelium as visualized by magnifying endoscopy with narrow-band imaging - Imamura, Kentaro; Yao, Kenshi; Hisabe, Takashi; Nambu, Masami; Ohtsu, Kensei; Ueo, Tetsuya; Yano, Shinji; Ishihara, Hiroshi; Nagahama, Takashi; Kanemitsu, Takao; Yamasaki, Kazutomo; Matsui, Toshiyuki; Tanabe, Hiroshi; Iwashita, Akinori; Daa, Tsutomu; Yokoyama, Shigeo; Matsunaga, Kazuhisa; Enjoji, Munechika (Endoscopy International Open, 2016)
Background and study aims: We previously reported our discovery of a white opaque substance (WOS) that is opaque to endoscopic light inside the epithelium while using magnifying endoscopy (ME) to examine gastric epithelial neoplasia. Histopathologic analysis revealed that the WOS comprises minute lipid droplets (LDs) accumulated within the neoplastic epithelium. In addition, the WOS was found in colorectal epithelial neoplasia, although it was unclear whether this WOS corresponded to an accumulation of LDs, as in the stomach. Therefore, the aim of the current study was to elucidate whether the WOS observed in colorectal epithelial tumors comprises LDs. Patients and methods: A consecutive series of 40 WOS-positive and 40 WOS-negative colorectal epithelial tumors was analyzed. One biopsy specimen was taken from each neoplasm. Cryostat sections were stained with oil red O for LD, and sections after formalin-fixation for LD were immunostained with anti-adipophilin antibody.Results: The prevalence of LDs stained with oil red O in WOS-positive vs. WOS-negative lesions was 47.5 % (19/40) vs. 5 % (2/40), respectively (P < 0.001). Furthermore, the WOS coincided with the expression of adipophilin; the prevalence of LDs stained by anti-adipophilin antibody in WOS-positive vs. WOS-negative lesions was 100 % (40/40) vs. 62.5 % (25/40), respectively (P < 0.001). Conclusions: This study elucidated for the first time that endoscopically visualized WOS in colorectal epithelial neoplasia may be composed of LDs accumulated in the neoplastic epithelium.